Generation of MHC class II:peptide ligands for CD4 T cell allorecognition of MHC Class II molecules - Leddon, Scott A. (2010)
PURPOSE OF REVIEW: The molecular and cellular mechanisms that underlie allorecognition of MHC class II molecules has been the subject much debate and experimentation in recent decades. In this review, we discuss several aspects of MHC class II structure, peptide acquisition and TcR-MHC:peptide interactions that have particular relevance to recognition of cells bearing allogeneic class II molecules. RECENT FINDINGS: First, MHC polymorphism is heavily biased toward those amino acids that influence stable peptide binding by MHC class II. Second, the peptide repertoire presented by class II molecules is highly diverse and can be edited substantially by the molecular catalyst HLA-DM and by tissue-specific expression of HLA-DO, stress and cytokines. Third, T cell receptor docking onto MHC peptide typically involves substantial contacts with the bound peptide in the MHC class II molecule. Finally, there is increasing evidence that T cell recognition of MHC is in part germline-encoded through T cell receptor V region contacts with MHC class II alpha helices. SUMMARY: Together, these conclusions support the view that allorecognition of MHC class II molecules is likely to parallel key aspects of conventional CD4 T cell recognition, with allele-dependent variation in peptide representation accounting in large part for the high precursor frequency of alloreactive CD4 T cells